Contribution of Renal and Non‐Renal Clearance on Increased Total Clearance of Adalimumab in Glomerular Disease. (29th June 2013) - Roberts, Brittney V.; Susano, Isidro; Gipson, Debbie S.; Trachtman, Howard; Joy, Melanie S.
Abstract The contribution of renal and non‐renal clearance toward targeted concentrations and/or effects of therapeutic proteins in nephrotic patients are unknown. This study dissected the contribution of clearance pathways to adalimumab elimination in patients with focal segmental glomerulosclerosis (FSGS). Urine was collected from seven patients treated with adalimumab. Renal clearance (ClR) was measured and non‐renal clearance (ClNR) was calculated as the difference between total clearance and ClR. Differences in cumulative amount in urine, ClR, and ClNR between study weeks 1 and 16 and relationships between proteinuria (protein:creatinine ratio (Up/c)), and ClR and ClNR were evaluated. Up to 13% of the adalimumab dose was lost in urine. ClNR contributed more than ClR to enhanced total clearance. There was a nonlinear relationship between Up/c and ClR (R2 0.7059); an increase in ClR beginning at Up/c of 12 mg/mg [slope 1.755, (C.I. −7.825 to 11.34)]. There was a linear relationship between Up/c and ClNR (R2 0.5039); for every one unit increase in Up/c, ClNR would increase by 3.5 mL/hr (P = 0.01). Both ClR and ClNR contribute to enhanced total clearance of adalimumab in glomerular disease secondary to FSGS. Additional research is needed to identify mechanisms for the increased ClNR pathways.